Sistemas publicitarios táctiles (2011)
Study and design of touch technologies with an emphasis on the viability of construction in a national brand focused on large-format advertising screens. The search for different touch systems in the world market is exposed and it is analysed which of these technologies is viable in Colombia based on economic and manufacturing criteria. The process of building a tactile membrane and the hardware necessary to adapt the system to a computer and software that interprets the coordinates is shown, and thus achieve a tactile interface.